Membangun Kampung Informatif : Pengabdian Masyarakat di Kampung Yensama, Oridek - Biak Numfor - Rahmat Nurjaman; Latif Karim; Alienra Davry Nanda Kadun MT (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Government regulation no. 60 of 1999 CHAPTER III Article 3 explains that every tertiary institution has duties and principals outlined in the Tri Dharma of higher education, namely: education and teaching, research and community service. These three main tasks are carried out intracurricularly, where they are very closely related to each other. There are many forms of community service activities that can be carried out by universities. Biak Regency has 19 districts and 257 villages. The Office Administration Management Study Program, FISIP, Cenderawasih University, as part of a higher education institution, has a strategic role in helping the community and building good relationships among the community in Yensama Village. So that physical development in the field in Oridek District, specifically in Yensama Village, can help the community in public service activities.